Menelusuri Makna Penamaan dan Bentuk Kaddoq Minynyaq Bugis dalam Perspektif Semiologi - Sari Hidayati; Nurhayati Rahman; Fathu Rahman; Muhlis Hadrawi; Ita Suryaningsih (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2022)
Food is one of the basic needs for fulfilling human nutrition. Especially in traditional food, the Bugis people have a habit of symbolizing the cultural cuisine they prepare. The purpose of this study is to explain the meaning of culinary through the name and form of kaddoq minynyaq. This is a descriptive qualitative study that employs Roland Barthes' semiology approach. The data collection technique applied was an interview technique with the aim of obtaining public opinion regarding the customs and beliefs of the Bugis tribe and the application of documentation techniques to obtain cultural archives in the form of images. Data analysis techniques began with data classification and continued with Roland Barthes' significance analysis. The results of this study are process-oriented; through the rampa aroma that is smeared on the kaddoq minynyaq culinary, it is hoped that the secret, in this case palliseq, will not be known by other people who do not know the people who carry out the tradition well. Through the analysis of témpa-témpa and kaddoq, it is hoped that society can uphold awareness of good behavior and the value of unity in order to obtain harmonious relationships.Keyword : Bugis, Kaddoq Minynyaq, Meaning, Naming, Shape